2019
DOI: 10.15406/jnsk.2019.09.00359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern and neuropsychologic outcome of moderate traumatic brain injuries treated in Conakry

Abstract: Cognitive impairment and behavioral changes following post-traumatic brain injury are disabling sequelae of traumatic brain injury. Processing speed, attention, executive functions and memory are usually the most impaired functions and may go unnoticed during a routine follow up neurologic consult. The aim of this study was to evaluate the degree of impairment of cognitive functions in a Guinean population of moderate traumatic brain injury by assessing the adaptability of classical Western neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…13 In most published series like the present, TBI was found to be predominant in young male. 14,15 Motor vehicle accidents (MVA) is the principal cause in our study and the most reported etiology in USA 16 and Australia. 17 The preponderance of moderate TBI (compared to mild TBI and severe TBI) in previous Guinean studies 4 as well as the current one is a direct consequence of the low level of development of local resources in neurosurgery.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…13 In most published series like the present, TBI was found to be predominant in young male. 14,15 Motor vehicle accidents (MVA) is the principal cause in our study and the most reported etiology in USA 16 and Australia. 17 The preponderance of moderate TBI (compared to mild TBI and severe TBI) in previous Guinean studies 4 as well as the current one is a direct consequence of the low level of development of local resources in neurosurgery.…”
Section: Discussionmentioning
confidence: 69%
“…During the study period 175 patients were treated in General Surgery for isolated moderate head injury. Of these, we were able to access data of 122 patients from our archives (69.7%) and 42 of them (34.4%) patients had available neurological and cognitive assessment data with a follow up of 9.7months (7)(8)(9)(10)(11)(12)(13)(14). Ten patients had motor and sensory sequelae, and 9 patients were not able to take the neuropsychological tests due to a profound impairment of their cognitive functions.…”
Section: Resultsmentioning
confidence: 99%